244 EXPLORING PUTATIVE PITX2C-DEPENDENT GENES IN MOUSE ATRIA. (24th May 2013) - Riley, G; Hopkins, S; Piccini, I; Brown, N; Fabritz, L; Kirchhof, P
Abstract : Paired-like homeodomain transcription factor 2 ( Pitx2 ) is involved in the embryonic left-right (L-R) patterning of heart and lung. So far, there is no known function for PITX2 in the adult heart. We recently demonstrated that Pitx2c is expressed highly and selectively in left atria of adult mice and humans compared to the right atria (Kirchhof et al ., 2011), indicative of a functional role for Pitx2c in the adult left atrium. Furthermore, there is a strong association between polymorphisms close to the PITX2 locus (on chromosome 4q25) and atrial fibrillation (AF) (Gudbjartsson et al ., 2007; Kaab et al ., 2009). We hypothesise that alterations in the L-R atrial expression ratio could promote the development of ectopic stimuli and AF. Gene array analysis previously identified a number of genes differentially regulated between left and right atria in wildtype adult mice (Kahr et al ., 2011). Indirect comparison with gene arrays performed in conjunction with these experiments, suggested that Ccl21, Ddit4l and Ppp1r1b were downregulated in the left atria of Pitx2c heterozygous mice, suggestive of downstream Pitx2-dependent expression in the adult left atrium. In this current work we have sought to quantify differential expression levels of Chemokine ligand 21 ( Ccl21 ); DNA damage-inducible transcript 4-like ( Ddit4l ); Pleckstrin homology-like domain family A, member 1 ( Phlda1 ); Protein phosphatase 1 regulatory subunit 1B ( Ppp1r1b ); Scavenger receptor class A ( Scara5 ); Troponin I2 type 2 ( Tnni2 ) and Chemokine ligand 14 ( Cxcl14 ) by RT-PCR in the left and right atria of 18 mice (9 Pitx2c heterozygous and 9 litter mate controls) aged between 14-20wks. RT-PCR was performed using SYBR Green and the ΔΔCt Method. All genes were found to be differentially expressed between the left and right atria in both wildtype and Pitx2c heterozygous mice. There was a trend towards differential fold change reduction in the left atria of Pitx2c heterozygous mice compared to wildtype for all candidate genes. The L-R ratios between Ccl21 and Ddit4l differ significantly ( Ccl21 0.372, p=0.01; Ddit4l 0.275, p=0.04). Ddit4l encodes a protein involved in DNA-damage and hypoxia-induced cell death whilst disruption of the CCL21 pathway in mice improved myocardial dysfunction suggesting that CCL21 levels actively impact upon cardiac pathology. These results support the hypothesis that Ccl21 and Ddit4l are positively regulated by Pitx2c, and may suggest that Pitx2c maintains leftness in the adult atrium; hence the contribution of these genes to AF pathology warrants further investigation.